Modeling digital inequality in basic education: a system dynamics simulation of educational continuity - Barragán Moreno, Sandra Patricia; Lozano Galindo, Oscar Leonardo (Frontiers in Education, 2025)
IntroductionDigital inequality remains a persistent obstacle to achieving educational equity, particularly in socioeconomically vulnerable contexts. This study analyzes how unequal access to digital platforms affects educational continuity in early childhood, primary, and secondary education.MethodsA System Dynamics model of the Forrester type was developed to simulate the cumulative effects of structural variables (household income, teacher digital competence, school–family collaboration, and digital public policies) over a 10-year horizon. The model was parameterized using official Colombian educational data and literature-based coefficients, and 13 simulations were conducted under different socioeconomic, pedagogical, and policy scenarios.ResultsSimulation outcomes indicate that educational continuity is highly sensitive to variations in income levels, teacher training, and investment in digital policies. Low-investment and low-income conditions led to progressive declines in retention, while scenarios combining improved household income, teacher competence, and policy support produced multiplier effects, strengthening continuity and transition to higher education.DiscussionFindings reveal that digital access alone is insufficient to guarantee educational continuity. Instead, pedagogical quality, teachers’ digital skills, and school–family collaboration emerge as key mediating factors sustaining engagement and reducing dropout.ConclusionSystem Dynamics modeling provided a comprehensive understanding of the feedback loops and interdependencies linking digital inequality and educational continuity. The study offers evidence-based insights for policymakers to design integrated strategies that combine technological investment, pedagogical innovation, and family participation to promote equitable and sustainable educational trajectories.